SISTEM INFORMASI MANAJEMEN PROYEK KONSTRUKSI BERBASIS WEBSITE PADA PT JAYA KUSUMA - Amelia, Nyimas Melati Puti; Terttiaavini; Coyanda, John Roni (Jurnal Ilmiah Informatika Global, 2025)
This research aims to design and develop a Web-Based Construction Project Management Information System for PT Jaya Kusuma to address various challenges, such as manual project submissions, budget planning (RAB) calculations using Microsoft Excel, and inefficient project progress reporting. The system is designed using the Agile Development methodology to ensure flexibility and responsiveness to user needs. Key features include online project submission, automated RAB management, uploading of initial agreement and contract documents in PDF format, and real-time project progress monitoring, all of which are accessible to clients, managers, and supervisors. Additionally, the system provides graph-based reports, enabling directors to monitor project performance easily. The implementation results indicate that the system enhances business process efficiency, data transparency, and service quality for clients while reducing the risk of errors in construction project management.